Social innovation among young and upcoming entrepreneurs living in the marginalised communities in Malaysia - Raja Suzana Raja Kasim; Samsudin A. Rahim; Wan Nursafiah Wan Ibrahim; Zulazli Hashim; Abang Feizal Abang Ibrahim (2014)
This study examines the best practices of innovative young and upcoming entrepreneurs living in the marginalised communities in Malaysia in formulating their psychological characteristics in developing social enterprise model.It includes the capturing of both tacit and explicit entrepreneurial values in building social innovation moves among these communities. This model is deemed to be robust if the value of knowledge could be tapped abd documented within the context of the young social enterprise. Althought these young entrepreneurs are able to point out a number of good examples of innovative work, however these examples generally not the outcome of a cohesive integrated social enterprise frame-work. The research design is descriptive correlation with a total of 213 young and upcoming entrepreneurs participated and they were extracted from the directory of the Electoral System of the Election Commission of Malaysia. This sampling frame includes young people who had engaged in social innovation and small business in Miri, Sarawak and selected young communities within the East Coast region of Malaysia. The validity and reliability of items were analyzed using Rasch Measurement analysis. Both items and person measures suggest a reliability coefficient of 0.73 and 0.88 respectively. This early investigation revealed that the the model also supports the robustness of the Grameen principles that aimed to improve the social economic growth, and provides attractive incomes and amenities to the young people who live in the marginalised areas while raising their overall income level. Despites various mechanisms introduced by these samples to support their innovative practices in managing small business and their social business values and services to communities, however, the findings also showed that specific policies oriented towards achieving the success of social enterprise embracing innovative higher-growth was lacking. This research had contributed to both sound practical and theorical aspects of social business value